Liberalized Trade and Worker-Firm Matching - Carl Davidson; Fredrik Heyman; Steven Matusz; Fredrik Sjöholm; Susan Chun Zhu (Lund University, School of Economics and Management, Department of Economics, 2012)
Recent theoretical analysis suggests that a reduction in the cost of exporting increases the degree of assortative matching between workers and firms in export-oriented industries. Changes that reduce the cost of imports have an ambiguous impact on matching. We combine detailed Swedish matched worker-firm data from 1995 – 2005 with tariff data to test these hypotheses. The data cover 94 sectors subject to international competition and includes all firms with at least 20 employees. Our findings strongly support the theoretical predictions.
Keywords: F14; F16; J20; 330; Matching; Globalization; Firms; Workers; Multinational Enterprises; International Trade